AFRICAN HUMAN MOBILITY REVIEW - Crush, Jonathan (African Human Mobility Review, 2021)
On a recent visit to Washington DC, I had an animated discussion with a taxi driver who was an avid supporter of Donald Trump. The driver was not the stereotypical white, middle-aged, small-town, working-class, non-collegeeducated, angry voter who put Trump in the White House. Rather, he was a former television producer and poet from India who had immigrated to the US in the 1990s, and was adamant that Trump would stop the â€œflood of illegal aliensâ€ into the country. His vigorous defence of Trump was a surprise, as was his buy-in to Trumpâ€™s anti-immigrant discourse of threat. There are few issues in the contemporary world that generate so much uninformed debate and misinformation as immigration (Blinder, 2015; de Haas, 2008; Hellwig and Sinno, 2017; Valentino et al., 2013).